Foundry Polymer-Based Inverted-Rib Waveguides - Malheiros-Silveira, G. N. [UNESP] (2018)
Development of polymer inverted-rib waveguides based on high-volume CMOS foundry process is presented. Simulation of waveguiding structures using a basic inverted waveguide manufacturing process showed that viable devices can be obtained. Full wafers were processed at the foundry's 150 mm-facility. Photomask layout and manufacturing as well as wafer post-processing and characterization were carried out. As preliminary results, spectral filters based on integrated ring resonators with free spectral range (FSR) of 1 nm are presented.